Quantitative assessment of contrast-enhancement patterns of the healthy dental pulp by magnetic resonance imaging: a prospective in vivo study - Jürchott, Alexander; Jelinek, Constanze; Kronsteiner, Dorothea; Jende, Johann; Kurz, Felix T.; Bendszus, Martin; Heiland, Sabine; Hilgenfeld, Tim (International endodontic journal, 2022)
Aim This prospective in vivo study aimed to optimize the assessment of pulpal contrast-enhancement (PCE) on dental magnetic resonance imaging (dMRI) and investigate physiological PCE patterns. Methodology In 70 study participants, 1585 healthy teeth were examined using 3-Tesla dMRI before and after contrast agent administration. For all teeth, the quotient of post- and pre-contrast pulp signal intensity (Q-PSI) was calculated to quantify PCE. First, pulp chambers were analysed in 10 participants to compare the coefficient of variation of mean versus maximum Q-PSI values (Q-PSImean versus Q-PSImax). Second, dynamic PCE was evaluated in 10 subjects to optimize the time interval between contrast agent application and image acquisition. Finally, 50 participants (age groups: 20-29, 30-39, 40-49, 50-59 and 60-69 years) were examined to analyse age, gender, tooth types and maxilla versus mandible as independent factors of PCE. Statistical analysis was performed using Wilcoxon signed rank test and linear mixed models. Results PCE assessment based on Q-PSImax was associated with a significantly smaller coefficient of variation compared with Q-PSImean, with median values of 0.17 versus 0.21 (p = .002). Analysis of dynamic PCE revealed an optimal timing interval for image acquisition 4 min after contrast media application. No significant differences in PCE were observed by comparing age groups, female versus male participants and maxillary versus mandibular teeth (p > .05). Differences between tooth types were small (median Q-PSImax values of 2.52/2.32/2.30/2.20 for molars/premolars/canines/incisors) but significant (p < .05), except for the comparison of canines versus premolars (p = .80). Conclusions PCE in dMRI was a stable intra-individual marker with only minor differences between different tooth types, thus forming an important basis for intra-individual controls when assessing teeth with suspected endodontic pathosis. Furthermore, it was demonstrated that PCE is independent of age, gender and jaw type. These findings indicate that dMRI-based PCE analysis could be a valuable diagnostic tool for the identification of various pulp diseases in future patient studies.